"Knapping, My Child, is Made of Errors": Apprentice Knappers at Swan Point and Little Panguingue Creek, Two Prehistoric Sites in Central Alaska. (2nd January 2021) - Gómez Coutouly, Yan Axel; Gore, Angela K.; Holmes, Charles E.; Graf, Kelly E.; Goebel, Ted
ABSTRACT: In Beringia, as in many other parts of the world, stone tools are the main diagnostic cultural artifact for understanding prehistoric societies. The analysis of lithic assemblages is the basis for establishing connections between sites and techno-complexes. Through highlighting major technological trends, archaeologists are able to interpret processes such as cultural continuity and migrations. Here we present a fine-grained analysis of two assemblages to perceive in detail the individuals behind the lithic productions, more specifically apprentice knappers. Although recognition of apprenticeship in a prehistoric context is not new, this is the first such study for Alaska and Beringia. We focus on two distinct assemblages with microblade technology: the late Pleistocene component of Swan Point CZ4b (Tanana valley) and the early Holocene component of Little Panguingue Creek C2 (Nenana valley), both in central Alaska.